Abundance, breeding and growth of the ocypodid crab Dotilla myctiroides (Milne-Edwards) on a West Malaysian beach - Hails, A. J.; Yaziz, S. (Elsevier Ltd., 1982)
The ocypodid crab, Dotilla myctiroides, was studied on the south-west coast of peninsular Malaysia. The mean numbers and biomass over a year along a transect from high to low water ranged from 37·5 to 579 crabs m-2 and from 2·22 to 50·79 g m-2 (wet weight) respectively. Berried females were found in all months of the year but two peaks of activity were apparent, from November to February and May to July. It is suggested that this may be related to changes in food abundance associated with the effects of monsoon winds on sea currents. Laboratory growth studies indicated that maximum life span was approximately 13 months (from first crab stage) for males and 10 months for females. Growth rate decreased with increasing size of crab. Egg number increased with size of female. © 1982.